(untitled) (Journal of Parents and Teachers, 2023)
In the Liaison Classrooms, male and female students from different backgrounds and ages between 10 and 17, who do not know the Spanish language, coexist. Its main objectives as they appear in the regulations that regulate them are: to teach the Spanish language, shorten the period of incorporation into the educational system and promote the development of their identity and personal integration.